Puerperium and Lactation: The Crucial Phases of Maternal and Infant Health - Rehan Haider; Asghar Mehdi; Anjum Zehra (PT FORMOSA CENDEKIA GLOBAL, 2024)
Puerperium and lactation are critical phases in a woman's life and are characterized by profound physiological and psychological changes. The puerperium, commonly known as the postpartum period, refers to the number of weeks following childbirth when a woman's body undergoes a series of adjustments to return to its non-pregnant state. This phase typically lasts for approximately six weeks but can vary from woman to woman. During puerperium, the uterus contracts, lochia (postpartum discharge) is expelled, and the body gradually recovers from the stress of pregnancy and childbirth. Emotional well-being is also an essential aspect of puerperium, as women often experience a range of emotions and adjustment challenges. Conversely, lactation is the process of producing and providing breast milk to the infants. It is a unique and essential aspect of motherhood, offering numerous health benefits for both the mother and baby. Lactation is primarily regulated by hormones, such as prolactin and oxytocin. Prolactin stimulates milk production, whereas oxytocin triggers milk ejection during breastfeeding. During lactation, the mother's body provides infants with vital nutrients, immunological protection, and emotional bonds through breastfeeding. This natural process also promotes uterine involution, helping the mother recover more quickly after childbirth. Furthermore, breastfeeding has far-reaching health benefits, reducing the risk of various diseases in both mothers and babies